2011
DOI: 10.1007/s11664-011-1810-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al Nanoparticles on the Microstructure, Electrical, and Optical Properties of AZO/Al/AZO Trilayer Thin Film

Abstract: In this work, designed growth of aluminum (Al)/aluminum-doped zinc oxide (AZO), AZO/Al/AZO, and AZO/Al multilayer electrodes by radiofrequency (RF) magnetron sputtering on glass substrates was studied. The microstructures, optical properties, and electrical characteristics of the multilayer electrode thin films were analyzed, their structural denseness and thickness were observed by field-emission scanning electron microscopy (FE-SEM), and their crystal orientation was identified by x-ray diffraction (XRD). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As a transparent conductive oxide, zinc oxide (ZnO) is a wide-bandgap semiconductor with high transmittance in the visible range [1,2], which has led to its broad application in the fields of flat panel displays, camera tubes, solar cells, organic light-emitting diodes, liquid crystal displays and so on [3,4]. However, pure ZnO has a high resistivity and cannot meet the requirements of transparent conductive films due to two mutually restrictive factors: high transmittance and low resistivity in the visible light range.…”
Section: Introductionmentioning
confidence: 99%
“…As a transparent conductive oxide, zinc oxide (ZnO) is a wide-bandgap semiconductor with high transmittance in the visible range [1,2], which has led to its broad application in the fields of flat panel displays, camera tubes, solar cells, organic light-emitting diodes, liquid crystal displays and so on [3,4]. However, pure ZnO has a high resistivity and cannot meet the requirements of transparent conductive films due to two mutually restrictive factors: high transmittance and low resistivity in the visible light range.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, hollow nanostructures that are singleshelled, double-shelled, and multi-shelled have been attracting considerable interest because of their unique properties such as low density, high specific surface area, and controllable surface permeability, [4][5][6] and their potential applications in various fields of biotechnology, chemistry, and advanced functional materials. [7][8][9][10][11][12] Photoluminescence studies have been reported for different tri-layer (core/shell/shell) semiconductor nanoparticles such as CdS/HgS/CdS, 13 Al doped ZnO/Al/Al doped ZnO thin films, 14 and hollow bi-layers nanoparticles such as ZnS/Ag 2 S 15 and PSA/SiO 2 . 16 Furthermore, doping of core/shell or hollow structures helps to enhance or develop new properties.…”
Section: Introductionmentioning
confidence: 99%
“…Yun et al reported that the combination of ITO/Ni/AZO enhanced the electrical conductivity, mobility, and the carrier concentration [11]. Other combinational structures having different metal layers such as ITO/Au/ITO [12], TCO/Ag/ TCO [13][14][15], AZO/Mo/AZO [16], and AZO/Au/AZO [17] were also reported. Each combination has its own individuality in enhancing overall performance of the device.…”
Section: Introductionmentioning
confidence: 99%